Mobile Recommendation System to Provide Emotional Support and Promote Active Aging for Older Adults in the Republic of Panama - Navarro, Nila; Cedeno-Moreno, Denis; Lopez, Victor; Matus, Ericka; Núñez, Ivonne; Concepción, Dimas H. (International Journal of Interactive Mobile Technologies (iJIM), 2024)
Aging brings with it physical and cognitive changes that can lead to health problems such as chronic disease and cognitive impairment. Technology is a fundamental ally in improving the quality of life of older adults by enabling accurate and early diagnosis. In this context, we present a mobile application designed to provide emotional support and guidance, thus contributing to the well-being of this demographic group. Our study was based on quantitative research methods, using an experimental approach on a sample of users aged between 60 and 80 years. The results showed that 93.3% of users found the app to be a useful resource for adopting a healthier lifestyle. The app provides specific recommendations, such as breathing exercises to reduce anxiety, recreational activities, exercises tailored to physical ability, and meditation practices. These specific features have been shown to improve the well-being of older adults by providing a personalized approach to the challenges of aging.